2014
DOI: 10.1002/2014jc009990
|View full text |Cite
|
Sign up to set email alerts
|

Storm tracks in the Southern Hemisphere subtropical oceans

Abstract: Ocean storm tracks have previously been associated with the midlatitude western boundary currents (WBCs) and the Antarctic Circumpolar Current (ACC). Here we identify and examine large-scale baroclinically unstable waves occurring within waveguides associated with potential density gradients in the subtropical regions of the Southern Hemisphere (SH) oceans where the trade winds and westerlies meet and at depths associated with mode water formation. In contrast to the Northern Hemisphere subtropics, the SH path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 85 publications
(123 reference statements)
6
50
2
1
Order By: Relevance
“…However, some recent work has focused on the observed inhomogeneity of the Southern Ocean's eddy field. This result is supported by O'Kane et al (2014), who demonstrated in an eddy permitting GCM that baroclinic disturbances generated in the subtropics were able to propagate and influence the eddy field long distances from their genesis regions. They concluded that the eddy field is, at least partially, set by nonlocal effects, such as eddies or energy propagating into a region from afar.…”
Section: B Storm Tracks In the Southern Oceansupporting
confidence: 52%
See 1 more Smart Citation
“…However, some recent work has focused on the observed inhomogeneity of the Southern Ocean's eddy field. This result is supported by O'Kane et al (2014), who demonstrated in an eddy permitting GCM that baroclinic disturbances generated in the subtropics were able to propagate and influence the eddy field long distances from their genesis regions. They concluded that the eddy field is, at least partially, set by nonlocal effects, such as eddies or energy propagating into a region from afar.…”
Section: B Storm Tracks In the Southern Oceansupporting
confidence: 52%
“…Unlike in the midlatitude atmosphere (Danielson et al 2006) and the subtropical oceans (O'Kane et al 2014), the propagation of coherent eddies does not significantly contribute to the downstream development of the storm track. In contrast to the commonly assumed mechanism (described in WWH07) of individual eddies forming in the regions of high baroclinicity and then propagating downstream into the regions of low baroclinicity, our mechanism posits that both the growth and decay of eddies occurs in the low baroclinicity regions, which, if true, would have implications for the parameterization of eddy tracer flux.…”
Section: A Summarymentioning
confidence: 95%
“…O'Kane et al . [, section 4.2.3 and associated supporting information], applying complex empirical Orthogonal Functions (CEOFs) and other methods to baroclinic disturbances in the South Pacific Ocean, found that CEOF modes 2–4 explain approximately 25% of the variance and that modes 3 and 4 propagate westward from the southeast Pacific to the eastern boundary of the Tasman Sea (PX06). They further show that once these baroclinic disturbances reach the eastern boundary of the Tasman Sea they enter the EAC either directly or via the South Equatorial Current.…”
Section: Tasman Sea Baroclinic Instability and Pathwaysmentioning
confidence: 99%
“…Here our focus is on the stability of the EAC and its connection to the South Pacific subtropical ocean storm track described recently by O'Kane et al . [].…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, os ciclones extratropicais exercem grande influência em regiões de latitudes médias e altas (Hoskins & Hodges, 2005;O'Kane et al, 2014). Os ciclones extratropicais apresentam sua faixa de preferência de ocorrência entre os paralelos de 35° e 65° em ambos os hemisférios, e por isso são importantes componentes da circulação geral atmosférica, através do forte impacto que exercem nos processos de troca de calor, momentum e vapor d'água (Tings & Held, 1990;Justino, 2004).…”
Section: Introductionunclassified